Performance investigation of the S-rotors - Bhayo, B.A. (Institute of Physics Publishing, 2015)
This paper presents and discusses results from an experimental investigation of three models of wind S-rotors. Models 1 is modified from conventional Savonius rotor with a single stage and zero offsets zero overlaps; model 2 is three blade single stage wind rotor; and model 3 is double stage conventional Savonius rotor. The three models were designed, fabricated and characterized in terms of their coefficient of performance and dynamic torque coefficient. A special open wind simulator was designed for the test. The optimum parameters for the models were based on previous studies. The results showed that the model 1, model 2 and model 3 has the maximum power coefficient of 0.26, 0.17, and 0.21 at the correspondence tip speed ratio (TSR) of 0.42, 0.39 and 0.46, respectively. Model 1 is further optimized in terms of the aspect ratio resulting in improved power coefficient by 24. The maximum dynamic torque coefficient of model 1, model 2 and model 3 was found as 0.81, 0.56 and 0.67 at the correspondence minimum TSR of 0.28, 0.21 and 0.17, respectively. It was noted that the all three models have high torque coefficient because the models were tested at higher applied torque on the rotors.